Sicily '43 the first assault on fortress Europe - Holland, James 1970- (Atlantic Monthly Press, 2020)
"On July 10, 1943, the largest amphibious invasion ever mounted took place, larger even than the Normandy invasion eleven months later: 160,000 American, British, and Canadian troops came ashore or were parachuted onto Sicily, signaling the start of the campaign to defeat Nazi Germany on European soil. Operation HUSKY, as it was known, was enormously complex, involving dramatic battles on land, in the air, and at sea. Yet, despite its drama and its paramount importance to ultimate Allied victory, very little has been written about the 38-day battle for Sicily. Based on much new research, Sicily '43 offers vital new perspective on a major turning point in World War II. The characters involved-General George Patton and Field Marshal Bernard Montgomery among many-were as colorful as the battles across the scorching plains and above the peaks of Sicly were brutal. Among Holland's great skills is incorporating the experience of on-the-ground participants on all sides-from American colonel Jim Gavin, British major Hedley Verity, and Canadian lieutenant Farley Mowat to brigade commander Wilhelm Schmalz, Luftwaffe fighter pilot Johannes "Macky" Steinhoff, and Italian combatants, civilians, and mafiosi alike-giving readers an intimate sense of what occurred in July and August 1943. Emphasizing the significance of Allied air superiority, Holland overturns conventional narratives that have criticized the Sicily campaign for the slowness of the Allied advance and that so many German and Italian soldiers escaped to the mainland; rather, he shows that clearing the island in 38 days against geographical challenges and fierce resistance was an impressive achievement. A powerful and dramatic account by a master military historian, Sicily '43 fills a major gap in the narrative history of World War II"--
Keywords: Sizilien -- Landung -- 1943; World War, 1939-1945 / Campaigns / Italy / Sicily; Operation Husky, 1943; Sicily (Italy) / History, Military / 20th century; Sicily (Italy) / History / 1870-1945; Military campaigns; Italy / Sicily; 1870-1999; History; Military history